Artificial Ground Freezing Impact on Shear Strength and Microstructure of Granite Residual Soil Under an Extremely Low Temperature - An, Ran; Zhang, Xianwei; Kong, Lingwei; Gong, Jianwu; Lei, Xuewen (Frontiers in Earth Science, 2021)
Artificial Ground Freezing (AGF) method, which is widely used in the tunnel excavations, significantly affects the properties of geotechnical materials in frozen-walls under an extremely low temperature. The undisturbed specimens of granite residual soil (GRS) were performed a freezing procedure at the temperature of -30℃ and a thawing procedure at the temperature of 25℃ to simulate AGF effects. Subsquently, triaxial (TRX) tests were conducted to evluate the mechaniacal properties and Nuclear Magnetic Resonance Image (NMRI) technique was applied to detect pore distributions. To clarify the pore viriations of GRS after freezing-thawing, the relaxation time (T2) distribution curves and T2-weighted images from NMRI results were throughly analyzed from the perspective of quantization and visualization. Results show that the shear strength as well as the cohesion of GRS are reduced sharply by AGF process, while the internal friction angle only decreases gently. The pore size distributions (PSD) converted from T2 curves are constituted of two different peaks, corresponding to micro-pores with diameters from 0.1 to 10 µm and macro-pores with diameters from 10 to 1000 µm. Under the AGF impact, the expansions in macro-pores and shringkage in micro-pores simultaneously exist in the specimen, which was verified from a visualized perspective by T2-weighted images. The frost heaving damage on mechnical property is attributed to the of microstructural disturbance caused by the presence of large-scale pores and uneven deformations in GRS subjected to AGF impact under an extremely low temperature.